Battery Life Cycle Sustainability: a Qualitative Study on Life Cycle Assessment Process Development at IONCOR - Somero, Emmi (My University, 2026)
The purpose of this study is to examine the EU Battery Regulation 2023/1542 requirements for a battery carbon footprint, study how environmental regulations impact sustainability practice adoption, and how to implement new sustainability practices successfully. The aim is to propose a process which battery manufacturers can leverage when calculating a battery carbon footprint and provide information of successful implementation tools of internal sustainability drivers and Lewin’s planned approach and examine the impacts of environmental regulations. An examination of the battery industry and its sustainability is conducted, after which the regulatory requirements for a battery carbon footprint from the EU Battery regulation 2023/1542 are described. This provides a background for the LCA process development to be developed on. To support a successful implementation, literature review of change management on regulatory impacts, internal sustainability drivers, and Lewin’s planned approach to change is presented. The literature review shows that regulations can positively impact the environmental performance of a company, while regulatory uncertainty negatively impacts the adoption of new sustainability practices. It also provides internal sustainability drivers and a change process to examine for applicability in the context of this thesis. The results of the empirical action research study provide a process guide for a battery carbon footprint calculation, and tools for successful implementation. The findings show new insights to the existing literature as well. The findings of previous literature on the impacts of regulations are largely confirmed, with results showing positive impacts of environmental regulations on environmental performance and sustainability practice implementation, and negative impacts of regulatory uncertainty. The results also bring interesting additions to the internal sustainability drivers. Dependencies between the internal sustainability drivers are identified, providing new thoughts regarding the magnitude of each driver.

Tämän tutkimuksen tarkoitus on tutkia EU Akkuasetuksen 2023/1542 vaatimuksia akun hiilijalanjäljen laskentaan, tutkia kuinka ympäristölainsäädännöt vaikuttavat vastuullisuustoimien käyttöönottoon, ja kuinka implementoida uusia vastuullisuustoimia onnistuneesti. Tavoitteena on tarjoa prosessimalli, mitä akkuvalmistajat pystyvät hyödyntämään laskiessaan akkujen hiilijalanjälkiä, tarjota informaatiota onnistuneen prosessikäyttöönoton saavuttamiseksi tutkimalla sisäisiä vastuullisuusajureita, sekä tutkia Lewinin järjestelmällistä lähestymistapaa muutokseen. Lisäksi tutkitaan ympäristölainsäädännön vaikutuksia uusien vastuullisuustoimien käyttöönotossa. Akkuteollisuuden ja sen vastuullisuuden läpileikkaus, sekä EU:n Akkuasetuksen 2023/1542 asettamien akkujen hiilijalanjälkivaatimusten läpikäynti tarjoavat pohjan elinkaariarviointiprosessin kehittämiselle. Onnistuneen prosessikäyttöönoton saavuttamiseksi toteutetaan kirjallisuuskatsaus valituista muutosjohtamisen käsitteistä. Tutkielmassa tutkitaan lainsäädännöllisiä vaikutuksia, sisäisiä vastuullisuusajureita, sekä Lewinin muutosmallia. Kirjallisuuskatsaus osoittaa, että lainsäädäntö voi positiivisesti vaikuttaa yrityksen ympäristölliseen suorituskykyyn, kun taas lainsäädännöllinen epävarmuus vaikuttaa negatiivisesti uusien vastuullisuustoimien käyttöönottoon. Katsaus tarjoaa myös tietoa sisäisistä vastuullisuusajureista ja muutosmallin tutkittavaksi tutkielman kontekstissa. Empiirisen tutkimuksen tulokset tarjoavat prosessiohjeen akkujen hiilijalanjäljen laskemiseen, sekä työkaluja onnistuneeseen käyttöönottoon. Löydökset tarjoavat uusia näkökulmia olemassa olevaan kirjallisuuteenkin. Olemassa olevan kirjallisuuden tunnistamat löydökset lainsäädännön vaikutuksista tunnistetaan myös tutkielmassa, kun tulokset osoittavat lainsäädännön kohentavan ympäristöllistä suorituskykyä, ja lainsäädännöllisen epävarmuuden tuovan negatiivisia vaikutuksia. Tulokset kuitenkin tarjoavat kirjallisuuteen myös uusia näkemyksiä. Riippuvuuksia olemassa olevien sisäisten vastuullisuusajurien välillä havainnoidaan, mikä tarjoaa uusia ajatuksia myös ajurien merkityksellisyysjärjestykseen.
Keywords: life cycle assessment; battery; carbon footprint; internal sustainability drivers; environmental regulations; Lewin’s planned approach